FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - William, Theofilus; Suryanto (E-Jurnal Akuntansi TSM, 2025)
This study aims to examine the influence of Return on Assets, Leverage, Firm Size, Sales Growth, Capital Intensity, Transfer Pricing, Audit Committee, and Institutional Ownership on Tax Avoidance. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023.The method used in this study is purposive sampling, resulting in a sample of 65 companies with a total of 195 data points. The data analysis method employed is multiple linear regression, using SPSS version 25 as the analytical tool. The results of this study indicate that Return on Assets, Sales Growth, and Capital Intensity have an effect on Tax Avoidance, while Leverage, Size, Transfer Pricing, Institutional Ownership, and Audit Committee do not have an effect on Tax Avoidance.